ANALISIS KEPUTUSAN PEMBELIAN PRODUK TAS JIMS HONEY DI KOTA SAMARINDA - Mutiara Rahmah; Rahayu, Vitria Puri; Ellyawati, Noor (Jurnal Prospek: Pendidikan Ilmu Sosial dan Ekonomi, 2024)
Purchasing decisions are important for the sustainability of a business, this study aims to determine how purchasing decisions are made at the Jims Honey Store in Samarinda City. This study is a descriptive study with a quantitative approach, data collection using a questionnaire with a sample size of 30 people, while data analysis uses descriptive analysis. The results of the study showed that purchasing decisions at the Jims Honey store in Samarinda City were high with an average value of 4.11 which is categorized as high. This purchasing decision is measured by five indicators, namely problem recognition, information search, evaluation of various alternatives, purchasing decisions and post-purchase decisions, where the results of the study show that all of these indicators have high and very high values because they are responded positively by respondents. The indicator that is least lies in searching for information through friends, this is because various online platforms make it easier for consumers so they don't have to ask friends to get product information.